High-intensity nanosecond pulsed electric field effects on early physiological development in Arabidopsis thaliana - Wisuwat Songnuan (2018)
The influences of pulsed electric fields on early physiological development in Arabidopsis thaliana were studied. Inside a 4-mm electroporation cuvette, pre-germination seeds were subjected to high-intensity, nanosecond electrical pulses generated using laboratory-assembled pulsed electric field system. The field strength was varied from 5 to 20 kV.cm -1 and the pulse width and the pulse number were maintained at 10 ns and 100, respectively, corresponding to the specific treatment energy from 300 J.kg -1 to 4.5 kJ.kg -1 . Statistical analyses on the average leaf area 5 and 15 days following pulsed electric field treatment showed that the effects appear significant the second week after treatments with a maximum increase of 80% compared to the control (P < 0.01).